Efficient dye adsorption by highly porous nanofiber aerogels - Mousavi, Sara; Deuber, Fabian; Petrozzi, Sergio; Federer, Lukas; Aliabadi, Majid; Shahraki, Farhad; Adlhart, Christian (Colloids and surfaces. A, Physicochemical and engineering aspects, 2018)
[Display omitted] •Nanofiber aerogels (NFAs) were synthesized from electrospun nanofibers.•Adsorption capacity of the electrospun nanofiber membrane (NFM) was retained.•The open porous structure of the NFA significantly facilitates mass transport of fluids.•Pressure drop within the NFA is reduced by a factor of 40 compared to the NFM. Electrospun nanofiber membranes are frequently used in adsorption processes thanks to their high specific surface area, tailored surface functionality, and fiber uniformity. However, they are still facing challenges such as low mechanical stability and unfavorable mass transport properties. In this study, an ultra-light and robust 3D nanofiber aerogel (NFA) or nanofiber sponge with tunable porosity and flexibility was synthesized from short pullulan/polyvinyl alcohol/polyacrylic acid nanofibers using a freeze casting process followed by thermal crosslinking. We demonstrate time the application of such NFAs in batch and continuous adsorption systems and compare their performance with flat nanofiber membranes (NFM). The NFAs proved to be promising adsorbents for cationic dyes due to their high adsorption capacity (383 mg/g) and their reusability. Langmuir isotherm was a suitable model for describing the adsorption process. The endothermic system followed a pseudo second order kinetic model and intra-fiber adsorption is found to be involved in the adsorption process. Dye adsorption by 3D NFAs was four times faster than for the respective flat NFMs and when used in a continuous process as a deep-bed filter, the pressure drop through the NFA was reduced by a factor of 40 while maintaining equal adsorption performance as for the NFM.